Evaluation of four phenotypic methods for the rapid identification of methicillin resistant Staphylococcus aureus - Bandaru, Narasinga R.; Budati, Srinivas (International Journal of Research in Medical Sciences, 2017)
Background: Methicillin-resistant Staphylococcus aureus (MRSA), a superbug has been recognized as one of the major pathogens in hospitals as well as community settings. The prevalence of MRSA is 30–70% and many studies have suggested an alarming rate of infections caused by this organism. In spite of modern diagnostic procedures and technological advancement, infections caused by MRSA still remain difficult to diagnose in developing countries like India. We tried to evaluate four phenotypic methods for the rapid identification of methicillin resistant Staphylococcus aureus (MRSA). Methods: The present study was undertaken to evaluate the four phenotypic methods for the detection of MRSA by oxacillin disc diffusion, cefoxitin disc diffusion, HiCrome rapid MRSA agar and the latex agglutination test. Results: Among 542 Staphylococcus aureus isolated, 304 were methicillin resistant Staphylococcus aureus (MRSA) and remaining 238 were methicillin sensitive Staphylococcus aureus (MSSA). Hence, the prevalence rate of MRSA in our study was 56.09%. Cefoxitin disc diffusion was found to be more specific and sensitive than oxacillin disc diffusion where as both HiCrome Rapid MRSA Agar and the latex agglutination tests showed similar specificity and sensitivity. Conclusions: The cefoxitin disc diffusion method, as recommended by the Clinical and Laboratory Standards Institute (CLSI) was found to be a reliable method for MRSA detection but it should be supplemented with some other method like latex agglutination to enhance the isolation rate of MRSA. We recommend that along with cefoxitin disc diffusion with another reliable method, preferably latex agglutination should be routinely used in all microbiology diagnostic laboratories to detect MRSA which help for its control of spread.